THE EFFECT OF PRICE DISCOUNTS ON IMPULSIVE ONLINE PURCHASE DECISIONS - Tengku Syarifah Roviqoh; Supriati Supriati (Politeknik Negeri Batam, 2022)
The purpose of this study was to determine the effect of price discounts on impulsive buying decisions and how big the response or consumer interest in price discounts on online impulse buying decisions for Shopee application users at Bengkalis State Polytechnic students. The objects in this study are consumers who use the Shopee application at Bengkalis State Polytechnic students consisting of 24 men and 76 women. The type of research used in this research is associative research through sending questionnaires to 100 respondents using the non-probability sampling method with purposive sampling. The test results show that the price discount has a positive and significant effect on impulsive buying decisions, meaning that the price discount variable is one of the variables that can be used to measure impulsive buying decisions. The determinant coefficient (KD) is 0.221 or 22.1%, which means that price discounts affect impulse buying decisions by 22.1% while the remaining 77.9% is influenced by other variables not examined in this study.